Use of glass-resin composite fibers for reinforcing concrete

By using alkali-resistant glass-resin composite fibers, the shortcomings of concrete in terms of tensile strength and crack resistance are solved, uniform distribution of fibers and efficient alkaline environmental resistance are achieved, and the performance of concrete is significantly improved.

CN119630524APending Publication Date: 2025-03-14MICHELIN & CO (CIE GEN DES ESTAB MICHELIN)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380057070.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-15
Filing Date
2023-06-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing concrete has shortcomings in terms of tensile strength and crack resistance, and the metal fibers used are sensitive to corrosion, have high density, and are difficult to distribute evenly.

Method used

Alkaline-resistant glass-resin composite fibers are made of alkali-resistant glass wire containing 5% to 30% ZrO2 and crosslinked resin, and are made by vacuum degassing, impregnation, shaping and ultraviolet irradiation.

Benefits of technology

The fiber has a high maximum service temperature, good uniform distribution, reduced CO2 emissions and alkaline resistance, significantly improving the crack resistance and service life of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630524A_ABST
    Figure CN119630524A_ABST
Patent Text Reader

Abstract

The invention relates to a method for manufacturing a monofilament made of a glass-resin composite material, to a monofilament obtained by this method, to a drum comprising a plurality of these monofilaments, and to the use thereof for reinforcing concrete, for reducing the weight of concrete and for reducing or preventing cracking of concrete, the monofilament comprises filaments of alkali-resistant glass embedded in a crosslinked resin, the filaments of alkali-resistant glass comprising 5 to 30% by weight of ZrO2. The invention also relates to concrete comprising these monofilaments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a glass-resin composite fiber for reinforcing concrete and a method for obtaining the glass-resin composite fiber. Background Art

[0002] Concrete is arguably the most widely used building material today due to its high compressive strength, durability, longevity and resilience. Its properties make it the material of choice, especially in the fields of buildings, roads and engineering structures.

[0003] Concrete consists essentially of aggregates held together by a binder, most commonly Portland cement. To improve the properties of concrete, it is known to use additives such as ultrafine particles (e.g. silica fume), superplasticizers (also known as water-reducing plasticizers) or metal, synthetic or mineral fibers.

[0004] Although very resistant to compression, concrete has low tensile strength and tension is often accompanied by the appearance of cracks. To overcome this problem, it is known to use reinforcing fibers. Due to their mechanical properties, metal fibers are particularly useful for reinforcing concrete. Therefore, they are very widely used to make concrete more ductile and improve its resistance to cracking.

[0005] However, metal fibers have the disadvantage of being sensitive to corrosion, which can be detrimental to the life of the concrete comprising such fibers. In addition, their density is generally greater than 7.7 and therefore they cannot be evenly distributed in concrete with a lower density (metal fibers tend to sink under the effect of gravity, or even under the effect of vibration when the concrete is vibrated to remove any air bubbles that may have formed during the pouring process).

[0006] To address this problem, it has been proposed to use synthetic fibers instead of metal fibers. However, the mechanical strength of these fibers (e.g. elastic (Young's) modulus, tensile strength) is not as good as that of metal fibers. In addition, their operating temperature (usually between 100°C and 160°C) is much lower than that of metal fibers (approximately between 600°C and 900°C), which may limit their use in certain applications.

[0007] Therefore, it would still be advantageous to have fibers that are corrosion resistant (to increase the service life of the concrete) and have improved mechanical properties (to improve crack resistance) compared to current non-metallic fibers. Summary of the invention

[0008] In conducting research, the applicant unexpectedly found that the above-mentioned problems can be solved by using specific alkali-resistant glass-resin composite fibers.

[0009] The Applicant has also observed many advantages obtained with the fibers according to the invention. Compared with the fibers of the concrete of the prior art, they are very easy to implement, in particular in the stage of mixing the various components of the concrete (easy to disperse), and in the stage of drying the concrete: since their density is close to that of the concrete, the fibers remain uniformly distributed in the concrete (they do not tend to sink like metal fibers whose density is greater than that of the concrete, nor do they tend to rise like synthetic fibers whose density is less than that of the concrete). The fibers of the invention also have a much higher maximum use temperature than the synthetic fibers currently used. In addition, the white color of the fibers according to the invention allows them to be used in light-colored concretes without affecting the aesthetics of these concretes. In addition, more generally, the use of the fibers according to the invention, due to their specific gravity and their reinforcing capacity, enables a significant reduction in the overall emission of CO2 for the same reinforcing level compared with the use of other fibers of the prior art. Finally, the use of alkali-resistant glass yarns provides the ability to withstand the alkaline environment of concrete, thus prolonging the time for which the fibers maintain their reinforcing effectiveness.

[0010] Therefore, the present invention relates to a method for manufacturing a glass-resin composite monofilament comprising an alkali-resistant glass filament embedded in a cross-linked resin, the alkali-resistant glass filament containing 5 to 30% by weight of ZrO2, the method comprising the following consecutive steps:

[0011] - forming a linear arrangement of alkali-resistant glass threads containing 5 to 30% by weight of ZrO2 and conveying this arrangement in the feed direction,

[0012] - degassing the arranged glass threads by the action of vacuum in a vacuum chamber,

[0013] - at the outlet of the vacuum chamber, after degassing, passing through a vacuum impregnation chamber to impregnate the arranged glass filaments with a photocurable resin composition in a liquid state (referred to as "impregnation resin"), thereby obtaining a prepreg comprising the glass filaments and the resin composition,

[0014] - passing the prepreg through a shaping die having a cross-section with a predetermined area and shape so as to give it a monofilament shape,

[0015] - Downstream of the die, the resin composition is polymerized under the action of ultraviolet rays in a UV irradiation chamber, the irradiation chamber comprising a tube transparent to ultraviolet rays (referred to as an irradiation tube), through which the monofilaments to be formed are passed and through which a stream of inert gas flows, the running speed of the monofilaments through the irradiation chamber (denoted as V ir ) is greater than 50m / min, the irradiation time of the monofilament in the irradiation chamber (expressed as D ir ) is equal to or greater than 1.5s,

[0016] - The monofilaments are cut into lengths ranging from 5 mm to 85 mm.

[0017] The invention also relates to a monofilament obtainable by the process according to the invention and to a tow comprising a plurality of monofilaments according to the invention.

[0018] The present invention also relates to the use of a monofilament according to the invention or a tow according to the invention for reinforcing concrete and / or reducing the weight of concrete and / or reducing or preventing cracking of concrete, and to concrete comprising a plurality of monofilaments according to the invention, the volume ratio of the monofilaments in the concrete preferably being in the range of 0.1% to 6%.

[0019] I-Definition

[0020] In the present application, unless expressly stated otherwise, all percentages (%) shown are percentages (%) by weight.

[0021] The expression "composition based on" is understood to mean that the composition comprises a mixture and / or in situ reaction products of the various components used, some of which are able and / or intended to react at least partially with one another during the various stages of manufacture of the composition; the composition may therefore be in a completely or partially crosslinked state, or in a non-crosslinked state.

[0022] In addition, any numerical interval represented by the expression "between a and b" means a numerical range extending from greater than a to less than b (i.e., excluding the end values ​​a and b), while any numerical interval represented by the expression "a to b" means a numerical range extending from a to b (i.e., including the strict end values ​​a and b). In the present application, when a numerical interval is represented by the expression "a to b", it is also preferably intended to represent the interval represented by the expression "between a and b".

[0023] All glass transition temperature "Tg" values ​​described herein are measured in a known manner by DSC (Differential Scanning Calorimetry) according to Standard ASTM D3418 (1999). BRIEF DESCRIPTION OF THE DRAWINGS

[0024] II-Brief description of the drawings

[0025] [ Figure 1 ] Figure 1 is a schematic diagram of a method for synthesizing a monofilament according to the present invention before cutting the monofilament to a given length.

[0026] [ Figure 2 ] Figure 2 (For ease of understanding, it is not shown to scale) is a diagram showing a cross section of a monofilament according to the present invention. DETAILED DESCRIPTION

[0027] III-Description of the Invention

[0028] The present invention therefore relates to a method for manufacturing a glass-resin composite (glass reinforced polymer or CVR for short) monofilament (or fiber, the two terms can be used interchangeably) comprising alkali-resistant glass filaments embedded in a cross-linked resin, the alkali-resistant glass filaments containing 5 to 30% by weight of ZrO2, the method comprising the following consecutive steps:

[0029] - forming a linear arrangement of alkali-resistant glass threads containing 5 to 30% by weight of ZrO2 and conveying this arrangement in the feed direction,

[0030] - degassing the arranged glass threads by means of a vacuum in a vacuum chamber,

[0031] - at the outlet of the vacuum chamber, after degassing, passing through a vacuum impregnation chamber to impregnate the arranged glass filaments with a photocurable resin composition in a liquid state (referred to as "impregnation resin"), thereby obtaining a prepreg comprising the glass filaments and the resin composition,

[0032] - passing the prepreg through a shaping die having a cross-section with a predetermined area and shape so as to give it a monofilament shape,

[0033] - Downstream of the die, the resin composition is polymerized under the action of ultraviolet rays in a UV irradiation chamber, the irradiation chamber comprising a tube transparent to ultraviolet rays (referred to as an irradiation tube), through which the monofilaments to be formed are passed and through which a stream of inert gas flows, the running speed of the monofilaments through the irradiation chamber (denoted as V ir ) is greater than 50m / min, the irradiation time of the monofilament in the irradiation chamber (expressed as D ir ) is equal to or greater than 1.5s, and this step finally obtains CVR monofilament,

[0034] - The monofilaments are cut into lengths ranging from 5 mm to 85 mm.

[0035] All the steps of the process of the invention (arranging, degassing, impregnation, shaping, polymerization, winding (where applicable) and cutting) are independently of one another known to the person skilled in the art, as are the materials used (multifilament fibers and resin composition); for example, they are described in either or both of the patent applications EP-A-1074369 and EP-A-1174250.

[0036] "Alkali-resistant glass threads" means threads of AR type glass. Such threads are well known to those skilled in the art and are different from threads of other types of glass, such as type E or type C. They are described, for example, in documents FR2644449A1, FR2907777A1 and JP2000178879.

[0037] Advantageously, the alkali-resistant glass threads contain 6 to 22%, preferably 10 to 20%, by weight of ZrO2.

[0038] Usually, glass yarn exists in the form of single multifilament fiber or multiple multifilament fibers connected to each other. In the case of multiple multifilament fibers connected to each other, the multifilament fiber is preferably substantially unidirectional. Each multifilament fiber can include tens, hundreds or even thousands of independent glass yarns. The average diameter of these extremely fine independent yarns is usually and preferably about 5 μm to 30 μm, more preferably 10 μm to 20 μm. The cross section of the independent yarn is preferably cylindrical.

[0039] As examples of alkali-resistant glass fibers that can be used in the context of the present invention, mention may be made of the "AR320S-720S", "AR640S-720S" or "AR1200S-720S" fibers of Nippon Electric Glass, the "Cem-fil" fibers of Owens Corning or the "HEJ 16.7%" fibers of Huierjie. A person skilled in the art knows very well how to adapt the application of dimensions to the surface of the filaments in order to improve the compatibility of the filaments with the resin used in the glass-resin composite.

[0040] By definition, the resins used are crosslinkable (ie curable) resins which can be crosslinked (cured) by any known method, in particular and preferably by UV (or UV-visible) radiation, preferably emitting in the spectrum ranging at least from 300 nm to 450 nm.

[0041] Here, the term "resin" or "resin composition" is understood to mean a resin in unmodified form, or any composition based on this resin and comprising at least one additive (i.e. one or more additives) before crosslinking. The term "crosslinked" resin is naturally intended to mean a resin that is cured (light-cured and / or heat-cured) in a state characteristic of "thermosetting" polymers (unlike "thermoplastic" polymers), in other words, in the form of a three-dimensional bond network.

[0042] Advantageously, the impregnating resin is based at least on:

[0043] - a crosslinkable resin selected from the group consisting of vinyl ester resins (preferably urethane vinyl ester resins), epoxy resins, polyester resins and mixtures thereof,

[0044] - a cross-linking system, preferably comprising a photoinitiator, which is reactive to UV radiation above 300 nm.

[0045] As crosslinkable resins, polyester resins or vinyl ester resins are preferably used, more preferably vinyl ester resins. "Polyester" resins are understood in a known manner to mean resins of the unsaturated polyester type. As for the vinyl ester resins, they are well known in the field of composite materials.

[0046] Without this definition being limiting, the vinyl ester resin is preferably of the epoxy vinyl ester type. More preferably, use is made of vinyl ester resins (especially of the epoxy type) based at least in part on phenolic resins (also called phenolics) and / or bisphenols (i.e. grafted onto structures of this type), i.e. preferably vinyl ester resins based on phenolic resins, bisphenols or phenolic resins and bisphenols.

[0047] Preferably, the initial tensile modulus of the resin measured at 23°C is greater than 3.0 GPa, more preferably greater than 3.5 GPa.

[0048] Epoxy vinyl ester resins based on phenolic resins (the part between square brackets in the following formula I) correspond, for example, in a known manner to the following formula (I):

[0049]

[0050] Epoxy vinyl ester resins based on bisphenol A (the part between square brackets in the following formula (II)) ("A" serves to indicate that the product is prepared using acetone) correspond, for example, to the following formula:

[0051]

[0052] Epoxy vinyl ester resins of the phenolic and bisphenol type show excellent results. As examples of such resins, mention may in particular be made of the vinyl ester resins "ATLAC 590" and "ATLAC E-Nova FW 2045" from the company AOC described in the above-mentioned patent applications EP-A-1074369 and EP-A-1174250 (diluted with about 40% styrene). Epoxy vinyl ester resins are available from other manufacturers, for example AOC (USA - "Vipel" resins).

[0053] The crosslinking system for the impregnating resin (resin composition) preferably comprises a photoinitiator, said photoinitiator being sensitive (reactive) to UV radiation above 300 nm, preferably between 300 nm and 450 nm. The photoinitiator is used in a preferred content of 0.5% to 3%, more preferably 1% to 2.5%. Preferably, the resin crosslinking system also comprises a crosslinking agent, for example a crosslinking agent in a content of between 5% and 15% (% by weight of the impregnating composition), said crosslinking agent being as defined above.

[0054] Preferably, the photoinitiator is from the family of phosphine compounds, more preferably a bis(acyl)phosphine oxide (e.g. bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (“Omnirad 819” from IGM or “SpeedCure BPO” from Lambson)), or a mono(acyl)phosphine oxide (e.g. “Esacure TPO” from IGM), which phosphine compounds can be mixed with other photoinitiators, such as photoinitiators of the α-hydroxyketone type (e.g. dimethylhydroxyacetophenone (e.g. “Omnirad 1173” from IGM) or 1-hydroxycyclohexylphenyl ketone (e.g. “Omnirad 184” from IGM)), benzophenone (e.g. 2,4,6-trimethylbenzophenone (e.g. “Esacure TZT” from IGM)) and / or thioxanthone derivatives (e.g. isopropylthioxanthone (e.g. “Esacure Omnirad ITX” from IGM)).

[0055] The crosslinking agent is preferably selected from the family of triacrylates.

[0056] According to the invention, it will be recalled in particular that, before any impregnation of the fibers, an essential step of degassing the arranged fibers by the action of a vacuum must be carried out, in order in particular to improve the effectiveness of the subsequent impregnation and in particular to ensure the absence of air bubbles in the final composite monofilament.

[0057] After passing through the vacuum chamber, the glass filaments enter an impregnation chamber which is completely filled with impregnation resin and is therefore free of air: in this sense, this impregnation step may be called "vacuum impregnation".

[0058] The mould, known as a "shaping" mould, is able to adjust the proportion of resin to glass fibre by having a cross section of a determined size (usually and preferably circular or rectangular) while giving the prepreg the desired shape and thickness of the filaments.

[0059] Advantageously, the diameter of the monofilaments leaving the shaping die ranges from 0.2 mm to 1.3 mm, preferably from 0.25 mm to 1.25 mm, preferably from 0.3 mm to 1.2 mm, so that the cut monofilaments obtained at the end of the method according to the invention exhibit these diameters.

[0060] The subsequent polymerization or UV irradiation chamber has the function of polymerizing or cross-linking the resin under the action of UV irradiation.

[0061] The UV irradiation chamber includes one or more UV irradiators (or radiators). Advantageously, the irradiation chamber includes a plurality of UV irradiators arranged in a row around the irradiation tube, i.e., at least two (two or more than two) UV irradiators. Each UV irradiator generally includes one (at least one) UV lamp (preferably emitting in a spectrum of 200nm to 600nm) and a parabolic reflector, the focus of the parabolic reflector being the center of the irradiation tube; the linear power density provided is preferably between 2000 watts / m and 14000 watts / m. Still more preferably, the irradiation chamber includes at least three, in particular at least four rows of UV irradiators.

[0062] Even more preferably, the linear power density provided by each UV irradiator is between 2500 Watt / m and 12000 Watt / m, in particular in the range of 3000 Watt / m to 10000 Watt / m.

[0063] UV irradiators suitable for the method according to the invention are known to the person skilled in the art and are available, for example, from the company Dr. UV radiators equipped with "UVAPRINT" lamps (iron-doped high-pressure mercury lamps) are sold by AG (Germany) under the reference "1055LCP AM UK". The nominal (maximum) power of each radiator of this type is equal to about 13,000 Watts, the power output being adjustable in practice by means of a potentiometer between 30% and 100% of the nominal power.

[0064] The diameter of the irradiation tube (preferably made of glass) is preferably between 10 mm and 80 mm, more preferably between 20 mm and 60 mm.

[0065] Between the shaping die and the final receiving support, the tension to which the glass fibers are subjected is preferably maintained at a moderate level, preferably between 0.2 cN / tex and 2.0 cN / tex, more preferably between 0.3 cN / tex and 1.5 cN / tex; in order to control this, these tensions can be measured directly at the exit of the irradiation chamber, for example by means of an appropriate tensiometer known to those skilled in the art.

[0066] The final CVR monofilament thus formed by passing through the UV irradiation chamber, wherein the resin is now in a solid state, is then recovered, for example, on a take-up drum, on which the final CVR monofilament can be wound to an extremely long length. Thus, the method may include a winding step for storing the monofilament after the monofilament has passed through the UV irradiation chamber and before the monofilament is cut.

[0067] Advantageously, the monofilaments coming out of the irradiation chamber (possibly after storage) are cut to obtain monofilaments having a length in the range of 10 mm to 80 mm, for example 15 mm to 60 mm.

[0068] The length / diameter ratio of the monofilaments obtained by the process according to the invention ranges advantageously from 10 to 110, preferably from 20 to 90, more preferably still from 25 to less than 80.

[0069] Particularly advantageously, the method of the present invention for producing CVR monofilaments comprises the following essential steps:

[0070] - The running speed of the monofilament through the irradiation chamber (V ir ) greater than 50m / min;

[0071] - The running time of the monofilament through the irradiation chamber (D ir ) is equal to or greater than 1.5s and equal to or less than 10s;

[0072] The irradiation chamber comprises a tube transparent to UV rays (for example a quartz tube or preferably a glass tube), called the irradiation tube, through which the monofilament to be formed runs and through which a flow of an inert gas (preferably nitrogen) is passed.

[0073] These combined steps enable the preferred improved properties of the CVR monofilaments of the present invention to be achieved, namely, in particular, improved Tg, elongation Ar and modulus (E and E') properties.

[0074] In particular, in the case where no inert gas (eg nitrogen) purging is used in the irradiation tube, it is observed that the above-mentioned properties of the CVR monofilaments deteriorate very rapidly during the manufacturing process, so that industrial performance can no longer be guaranteed.

[0075] In addition, if the irradiation time D of the monofilament in the irradiation chamber is ir If the irradiation time D of the monofilament in the irradiation chamber is too short (less than 1.5 s), many tests show that the resin is not fully cross-linked, resulting in poor mechanical properties (including breaking stress and flexural strength). ir Too long (eg greater than 10 s) and this increases the risk of the resin boiling, thereby creating more voids and compromising mechanical properties (including fracture stress).

[0076] It is therefore understood that due to the combination of the steps of the method according to the invention, in particular due to the step of degassing the arranged glass threads by the action of a vacuum in a vacuum chamber and the step of irradiating the glass threads at the above mentioned speed V in an irradiation tube through which a flow of inert gas passes. ir and the above irradiation time D ir The step of polymerization was followed to obtain a CVR monofilament with a porosity of less than 2% and a breaking stress of more than 1050 MPa.

[0077] [Table 1]

[0078]

[0079]

[0080] It is also observed that high irradiation speed V ir (greater than 50 m / min, preferably between 50 m / min and 150 m / min) is advantageous on the one hand for an excellent degree of alignment of the glass threads within the CVR monofilament and on the other hand for better maintenance of the vacuum in the vacuum chamber, thereby significantly reducing the risk of a certain amount of impregnation resin reaching the vacuum chamber from the impregnation chamber backwards and thus for a better impregnation quality.

[0081] Preferably, the speed V ir Between 50 m / min and 150 m / min, more preferably in the range of 60 m / min to 120 m / min.

[0082] Preferably, the irradiation time D ir Between 1.5 s and 10 s, more preferably in the range of 2 s to 5 s.

[0083] Another subject of the present invention is a CVR monofilament obtainable by the process according to the invention, preferably according to which:

[0084] - The running speed of the monofilament through the irradiation chamber (V ir ) greater than 50m / min;

[0085] - The running time of the monofilament through the irradiation chamber (D ir ) is equal to or greater than 1.5s and equal to or less than 10s;

[0086] the irradiation chamber comprises a tube transparent to ultraviolet rays (for example a quartz tube or preferably a glass tube), called the irradiation tube, through which the monofilament to be formed is passed and through which a flow of an inert gas (preferably nitrogen) is passed,

[0087] - The diameter of the CVR monofilaments is preferably in the range of 0.2 mm to 1.3 mm.

[0088] Thus, the CVR monofilaments obtainable by the process according to the invention comprise alkali-resistant glass filaments embedded in a crosslinked resin and have a length ranging from 5 mm to 85 mm. Furthermore, taking into account the specific steps of the process according to the invention, the monofilaments advantageously have a porosity of less than 2% and a breaking strength greater than 1050 MPa.

[0089] According to the invention, the porosity of the CVR monofilaments is advantageously less than 1%, preferably less than 0.5%. Advantageously, the porosity of the CVR monofilaments is between 0% and 2%, preferably between 0.01% and 1%, preferably between 0.05% and 0.5%.

[0090] The porosity can be measured by microscopy (e.g., scanning electron microscopy), preferably using area calculation software, such as the FIJI program. To perform the measurement, the following protocol is preferably performed:

[0091] - obtaining cross-linked CVR monofilaments,

[0092] - coating it with a cold coating resin, for example of the epoxy type, for example in a vacuum coating device (for example the CitoVac from the company Stuers),

[0093] - cutting the coated CVR monofilaments, for example using a hydraulic shear (for example "SH-5214" from the company Baileigh),

[0094] - polishing the cross section of the CVR monofilament, for example using a mechanical polisher such as from the company Mecapol, preferably to a final particle surface of 0.25 μm,

[0095] - Apply 1 nm to 4 nm of gold, for example using a gold sputter coater (e.g. from the company Cressington coater of series 108 or 208),

[0096] - observing the cross section of the CVR filament using a (15 kV) scanning electron microscope, preferably under vacuum, and

[0097] - Calculate the surface area percentage of porosity using an image processing program (eg FIJI).The term "porosity" of a CVR filament refers to any gas (particularly air) or void space present within the CVR filament.

[0098] According to the present invention, the breaking stress Cr of the CVR monofilament is advantageously greater than 1050 MPa, preferably greater than or equal to 1100 MPa, more preferably greater than or equal to 1200 MPa. Preferably, the breaking stress of the monofilament is between 1050 MPa and 1700 MPa, preferably 1100 MPa to 1600 MPa, more preferably 1200 MPa to 1500 MPa.

[0099] Advantageously, the initial tensile modulus (expressed as E 23 ) (also called Young's modulus) is greater than 35 GPa, preferably greater than or equal to 40 GPa. In particular, the E 23Preferably between 35 GPa and 50 GPa, preferably between 40 GPa and 49 GPa.

[0100] Mechanical tensile properties of CVR monofilaments (modulus E 23 , breaking stress Cr and breaking elongation Ar) can be measured in a known manner according to the protocol described in Section IV-1 below.

[0101] Furthermore, the CVR monofilament according to the present invention advantageously has the following properties:

[0102] - the glass transition temperature (expressed as Tg) of the crosslinked resin is equal to or greater than 190°C;

[0103] - the elongation at break of the monofilament measured at 23° C. (expressed as Ar) is equal to or greater than 3.0%, preferably greater than 4.0%;

[0104] - Initial tensile modulus of the monofilament measured at 23°C (expressed as E 23 ) is greater than 35 GPa, preferably greater than 40 GPa; and

[0105] The real part of the complex modulus of the single fiber measured by the DMTA method at 190°C (expressed as E' 190 ) is greater than 30GPa.

[0106] The glass transition temperature (expressed as Tg) of the crosslinked resin is preferably greater than 195° C., in particular greater than 200° C. In the present application, unless otherwise specifically stated, the glass transition temperature is measured in a known manner, for example by DSC (Differential Scanning Calorimetry) in the second scan according to standard ASTM D3418 of 1999 (DSC apparatus "822-2" from Mettler Toledo; nitrogen atmosphere; the sample is first raised from ambient temperature (23° C.) to 250° C. (10° C. / min), then rapidly cooled to 23° C., and then finally recording the DSC curve with a gradient of 10° C. / min from 23° C. to 250° C.).

[0107] The elongation at break (denoted as Ar) of the CVR monofilament measured at 23° C. is preferably greater than 4.0%, more preferably greater than 4.2%, in particular greater than 4.4%.

[0108] Modulus E' 190 Preferably greater than 33 GPa, more preferably greater than 36 GPa.

[0109] In order to achieve an optimal compromise between the thermal and mechanical properties of the CVR monofilament of the present invention, the ratio E' (Tg’-25) / E' 23 Advantageously greater than 0.85, preferably greater than 0.90, E' 23 and E'(Tg’-25) is the real part of the complex modulus of the monofilament measured by DMTA at a temperature expressed in °C, respectively, of 23 °C and equal to (Tg'-25), wherein the expression Tg' denotes the glass transition temperature, this time measured by DMTA.

[0110] Still more advantageously, the ratio E' (Tg’-10) / E' 23 Greater than 0.80, preferably greater than 0.85, E' (Tg’-10) is the real part of the complex modulus of the monofilament measured by DMTA at a temperature in °C equal to (Tg'-10).

[0111] E' and Tg' were measured using the "DMA" from ACOEM (France). + The 450" viscoanalyzer is carried out in a known manner by means of DMTA ("Dynamic Mechanical Thermal Analysis"), using the "Dynatest 6.83 / 2010" software to control the bending, tension or torsion tests.

[0112] According to the device, since the three-point bending test cannot input the initial geometric data of a monofilament with a circular cross section in a known manner, only a geometric shape with a rectangular (or square) cross section can be input. Therefore, in order to obtain an accurate measurement of the modulus E' of a monofilament with a diameter D, it is conventional to input a square cross section with a side length "a" and with the same surface moment of inertia into the software, so as to be able to operate with the same specimen stiffness R.

[0113] The following well-known relationship must be applied (E is the modulus of the material, I s is the surface moment of inertia of the object under consideration, and * is the multiplication symbol):

[0114] R=E 复合材料 *I 圆形截面 =E 复合材料 *I 正方形截面

[0115] Where: I 圆形截面 =π*D 4 / 64, and I 正方形截面 =a 4 / 12

[0116] The value of the side length "a" of an equivalent square having the same surface inertia as that of a (circular) cross section of a monofilament having diameter D can be easily deduced therefrom according to the following equation:

[0117] a=D*(π / 6) 0.25

[0118] In the case where the cross section of the tested sample is not circular (or rectangular), the same calculation method will be applied regardless of its specific shape and the surface moment of inertia I on the cross section of the tested sample will be determined in advance. s .

[0119] The tested specimen (usually of circular cross section and diameter D) has a length of 35 mm. It is arranged horizontally on two supports 24 mm apart. A repetitive bending stress is applied at a frequency of 10 Hz, in the form of a vertical displacement with an amplitude equal to 0.1 mm (therefore an asymmetric deformation, the interior of the specimen is subjected only to compressive stresses and not to tensile stresses), in the middle of the two supports, at right angles to the centre of the specimen.

[0120] Then, the following procedure was applied: under this dynamic stress, the specimen was gradually heated from 25°C to 260°C with a gradient of 2°C / min. At the end of the test, the measured values ​​of the elastic modulus E', the viscous modulus E" and the loss angle (δ) as a function of temperature were obtained (where E' is the real part of the complex modulus and E" is the imaginary part of the complex modulus); Tg' is the glass transition temperature corresponding to the maximum value (peak) of tan(δ).

[0121] Advantageously, the compressive elastic strain under bending is greater than 3.0%, more preferably greater than 3.5%, in particular greater than 4.0%.According to another preferred embodiment, the compressive fracture stress under bending is greater than 1050 MPa, more preferably greater than 1200 MPa, in particular greater than 1400 MPa.

[0122] The above-mentioned compressive bending properties are measured on CVR monofilaments by the method known as the loop test (D. Sinclair, J. App. Phys. 21, 380, 1950) as described in application EP 1167080. In the present case, a loop is produced and allowed to gradually reach its breaking point. The breaking properties (which are easily observed due to the large dimensions of the cross section) make it possible to immediately perceive that the CVR monofilament of the invention (which is subjected to bending stress until it breaks) breaks on the side where the material is stretched, which can be confirmed by simple observation. Taking into account the large dimensions of the loop in this case, the radius of the circle inscribed in the loop can be read at any time. The radius of the inscribed circle just before the breaking point corresponds to the critical radius of curvature (denoted by Rc).

[0123] The critical elastic strain (denoted as Ec) can then be determined by calculation from the following equation (where r corresponds to the radius of the filament, i.e. D / 2):

[0124] Ec=r / (Rc+r)

[0125] The bending compressive fracture stress (expressed as σ) was obtained by calculation using the following formula (where E is the initial tensile modulus):c ):

[0126] σ c =Ec*E

[0127] Since in the case of the CVR monofilament according to the invention the loop breaks at the portion under tension, it can be concluded that the compressive breaking stress is greater than the tensile breaking stress when bent.

[0128] Rectangular bars can also be fractured in bending by a method known as the three-point method (ASTM D 790). This method also allows visual confirmation that the nature of the fracture did occur in tension.

[0129] Advantageously, the breaking stress in pure compression is greater than 700 MPa, more preferably greater than 900 MPa, in particular greater than 1100 MPa. In order to avoid buckling of the CVR monofilaments under compression, this quantity is measured according to the method described in the publication "Critical compressive stress for continuous fiber unidirectional composites" by Thompson et al. (Journal of Composite Materials, 46 (26), 3231-3245).

[0130] Preferably, in the CVR monofilament of the present invention, the glass filaments are aligned to such an extent that more than 85% (number %) of the filaments have an inclination of less than 2.0 degrees, more preferably less than 1.5 degrees relative to the axis of the monofilament, the inclination (or misalignment) being measured as described in the above-mentioned publication of Thompson et al. It is also preferred that the CVR monofilament according to the present invention has no helical deformation, i.e. it is not twisted. In any case, the number of turns per meter of the CVR monofilament is less than 5, preferably less than 2, preferably less than 0.5, preferably from 0 to 0.5.

[0131] Preferably, the glass fiber (ie filament) weight content in the CVR monofilament is in the range of 65% to 85%, preferably 70% to 80%.

[0132] The weight content is calculated using the ratio of the count of the initial glass fiber to the count of the final CVR monofilament. The count (or linear density) is determined by weighing the length based on at least three samples (each sample corresponds to a length of 50 m); the count is given in tex (the weight in grams of 1000 m of product - as a reminder, 0.111 tex equals 1 denier).

[0133] Furthermore, the volume fraction of glass fibers in the CVR monofilament is advantageously in the range of 40% to 60%, preferably 45% to 55%.

[0134] The volume fraction of mineral fibers in the final CVR filament corresponds to the surface fraction of glass fibers of the cross section of the CVR filament relative to the total area of ​​the cross section of the CVR filament. The surface fraction of glass fibers can be determined in the same manner as described below for measuring porosity.

[0135] Furthermore, the crosslinked resin accounts for 15% to 35% by weight, preferably 20% to 30% by weight of the CVR monofilament of the present invention. Furthermore, the volume fraction of the resin in the CVR monofilament is advantageously in the range of 40% to 60%, preferably 45% to 55%. The weight percentage and volume fraction of the crosslinked resin can be obtained according to a method similar to that used to obtain the weight content and volume fraction of the above-mentioned glass fiber.

[0136] Preferably, the density (or mass per unit volume, in g / cm 3 The density is measured by a professional "PG503 DeltaRange" balance from the company Mettler Toledo (at 23° C.); several centimeters of the sample are weighed in turn in air and immersed in ethanol, and the device's software then determines the average density from three measurements.

[0137] The diameter D of the CVR monofilament of the present invention is preferably in the range of 0.2 mm to 1.3 mm, preferably between 0.25 mm and 1.25 mm, more preferably between 0.3 mm and 1.2 mm, in particular between 0.4 mm and 1.1 mm.

[0138] This definition covers both substantially cylindrical (with a circular cross section) monofilaments and monofilaments of other shapes, such as elliptical monofilaments (with a more or less flat shape) or monofilaments with a rectangular cross section. In the case of non-circular cross sections, unless otherwise specifically stated, by convention D is the diameter known as the gap diameter, i.e. the diameter of an imaginary cylinder of revolution around the monofilament, in other words the diameter of the circumscribed circle around its cross section.

[0139] Furthermore, the length L of the CVR monofilament of the present invention is preferably in the range of 10 mm to 80 mm, for example, 15 mm to 60 mm.

[0140] Advantageously, the length / diameter ratio L / D of the CVR monofilaments of the present invention is in the range of 10 to 110, preferably 20 to 90, still more preferably 25 to less than 80.

[0141] The invention also relates to a tow comprising a plurality of CVR monofilaments according to the invention and at least one element holding the monofilaments together. Preferably, the holding element is a rupturable film, such as a tearable, dispersible water-soluble film. Preferably, at least one holding element is a water-soluble thread.

[0142] Advantageously, the retaining element is a water soluble film, preferably made of a material selected from polyvinyl alcohol (PVA) or any water soluble or bioplastic polymer, such as a bioplastic derived from milk casein.Preferably, at least one water soluble film is made of a material selected from polyvinyl alcohol.

[0143] The tow according to the invention advantageously comprises a number of filaments in the range of 300 to 20,000.

[0144] The monofilaments constituting the tow may have the same or different sizes. For example, the tow may include monofilaments having different lengths, diameters and / or length-to-diameter ratios. Advantageously, the tow includes monofilaments according to the invention whose lengths and diameters differ from each other by no more than 10%, preferably by no more than 3%.

[0145] As mentioned above, the monofilaments according to the invention can be used in particular as additives for concrete. Therefore, the invention also relates to the use of the CVR monofilaments according to the invention or the tows according to the invention for reinforcing concrete and / or reducing the weight of concrete and / or reducing or preventing cracking of concrete.

[0146] Another subject of the invention is a concrete comprising a plurality of CVR filaments according to the invention.The concrete can be prepared by any technique known to a person skilled in the art.

[0147] Advantageously, the volume proportion of the monofilaments according to the invention in the concrete according to the invention is in the range from 0.1% to 6%, for example from 0.1% to 1.5% for "conventional" concrete (for example of type BPS C40 / 50XA3), or from 1.5% to 6% for ultra-high performance fiber reinforced concrete (UHPFRC).

[0148] An example of the manufacture of CVR monofilaments according to the invention and their use for reinforcing concrete is described below.

[0149] Attached Figure 1 An example of an apparatus 10 capable of producing a CVR monofilament according to the invention is schematically shown in a very simple manner.

[0150] In this figure, a reel 11a can be seen, which in the example shown comprises glass fibers 11b (in multifilament form). The reel is continuously unwound by a drive, so as to produce a rectilinear arrangement 12 of these fibers 11b. Usually, the reinforcing fibers are delivered as "rovings", i.e. groups of fibers that have been wound in parallel on a reel; for example, alkali-resistant glass fibers sold by Nippon Electric Glass under the fiber designation "AR1200S-920S" are used, whose count is equal to 1200 tex (as a reminder, 1 tex = 1 g / 1000 m of fiber). For example, the traction applied by the rotating receiver 26 will cause the fibers to advance in parallel and the CVR monofilaments to advance along the entire length of the device 1.

[0151] The arrangement 12 is then passed through a vacuum chamber 13 (connected to a vacuum pump (not shown)) arranged between an inlet pipe 13a and an outlet pipe 13b leading to an impregnation chamber 14, the two pipes preferably having rigid walls, for example having a minimum cross-section that is larger than the total cross-section of the fibers (typically twice as large) and a length that is much larger than the minimum cross-section (typically 50 times as large).

[0152] As already taught in the above-mentioned patent application EP-A-1174250, the use of tubes with rigid walls for the inlet to the vacuum chamber and the outlet from the vacuum chamber and for the transfer from the vacuum chamber to the impregnation chamber has proven to be compatible with high fiber throughput rates through the openings without breaking the fibers and also to ensure adequate sealing. Taking into account the fiber advance rate and the length of the tube, it is necessary (if experimentally necessary) to find the maximum flow cross-section that still allows adequate sealing, taking into account the total cross-section of the fibers to be processed. Typically, the vacuum in the chamber 13 is, for example, about 0.1 bar and the length of the vacuum chamber is about 1 meter.

[0153] On leaving the vacuum chamber 13 and the outlet pipe 13b, the arrangement 12 of fibers 11b passes through an impregnation chamber 14 comprising a feeding tank 15 connected to a metering pump (not shown) and a sealed impregnation tank 16 completely filled with an impregnation composition 17 based on a curable resin of the vinyl ester type (e.g. " E-Nova FW2045"). As an example, the composition 17 also contains (in a weight content of 1% to 2%) a photoinitiator suitable for UV irradiation and / or UV-visible irradiation, for example bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide ("Omnirad 819" from the company IGM), which is subsequently treated with the composition. It can also contain (for example about 5% to 15%) a crosslinker, for example tris(2-hydroxyethyl)isocyanurate triacrylate ("SR 368" from the company Sartomer). Of course, the impregnation composition 17 is in a liquid state.

[0154] Preferably, the impregnation chamber is several meters long, for example between 2 m and 10 m in length, in particular between 3 m and 5 m in length.

[0155] Thus, a prepreg comprising, for example (in wt. %) 65 to 75% solid fibres 11 b and the remainder (25 to 35%) formed by a liquid impregnation matrix 17 leaves the impregnation chamber 14 in a sealed outlet pipe 18 (still under rough vacuum).

[0156] The prepreg is then passed through a shaping device 19 comprising at least one shaping die 20, whose channel (not shown here) is, for example, circular, rectangular or even conical, adapted to the specific implementation conditions. As an example, the channel has a circular minimum cross section, the diameter of its downstream orifice being slightly greater than the diameter of the target monofilament. The length of the die is generally at least 100 times the minimum dimension of the minimum cross section. Its purpose is to give the finished product a good dimensional accuracy, and it can also be used to meter the fiber content relative to the resin. According to a possible embodiment variant, the die 20 can be incorporated directly into the impregnation chamber 14, so that, for example, the outlet pipe 18 is not required.

[0157] Preferably, the shaped area is several centimeters long, for example a length between 5 cm and 50 cm, in particular between 5 cm and 20 cm.

[0158] By means of the shaping means (19, 20), at this stage a "liquid" composite monofilament 21 is obtained (liquid in the sense that its impregnation resin is still liquid), the cross-sectional shape of which is preferably substantially circular.

[0159] Then, at the outlet of the shaping device (19, 20), the liquid composite monofilament 21 obtained in this way is polymerized by passing through a UV irradiation chamber (22) comprising a sealed glass tube (23) through which the composite monofilament travels; the tube, which is generally a few centimeters in diameter (for example 2 to 3 cm), is irradiated by a plurality (here for example 4) of UV irradiators (24) arranged in a row at a short distance (a few centimeters) from the glass tube (from Dr. "UVAprint" lamp with a wavelength of 200nm to 600nm).

[0160] Preferably, the irradiation chamber is several meters long, for example between 2m and 15m in length, in particular between 3m and 10m in length.

[0161] In this example, the irradiation tube (23) has a nitrogen gas flow flowing through the irradiation tube (23).

[0162] The irradiation conditions are preferably adjusted so that in the irradiation chamber the temperature of the CVR filaments measured at their surface (eg by a thermocouple) is greater than the Tg of the crosslinked resin (in other words, greater than 190°C) and more preferably less than 270°C.

[0163] After the resin polymerizes (cures), the CVR filament (25), now in a solid state and traveling in the direction of arrow F, then reaches its final take-up drum (26).

[0164] Finally, if Figure 2 Very simply shown, the finished composite material entity manufactured is obtained in the form of a continuous very long CVR filament (25) whose individual glass threads (251) are uniformly distributed throughout the volume of the cured resin (252). Its diameter is for example equal to about 1 mm.

[0165] Due to the above operating conditions, the process of the present invention can be carried out at a high speed greater than 50 m / min, preferably between 50 m / min and 150 m / min, more preferably in the range of 60 m / min to 120 m / min.

[0166] The continuous CVR monofilament (25) may be cut to a given length ( 100 mm) by any method known to those skilled in the art, such as using a hydraulic shear (e.g. "SH-5214" from Baileigh). Figure 1 The length of the monofilament is preferably 45 mm (not shown), for example 45 mm. This step can be carried out directly at the exit of the irradiation chamber (23). It can also be carried out after the monofilament is packaged on the final take-up drum (26). In this case, it is preferred to unwind the monofilament from the end of the monofilament that is most axially toward the outside of the drum, so as to avoid spiral deformation of the monofilament. This is because, if the monofilament is unwound from the end of the monofilament that is most axially toward the inside of the drum, this will cause the monofilament spiral to deform, which will be unfavorable for the breaking stress.

[0167] IV - Examples

[0168] IV-1 Measurements and Tests Used

[0169] Porosity (%)

[0170] The porosity was measured according to the following protocol:

[0171] - obtaining cross-linked CVR monofilaments,

[0172] - coating it with a cold coating resin of epoxy type in a vacuum coating device (CitoVac from the company Stuers),

[0173] - cutting the coated CVR monofilaments using a hydraulic shear (SH-5214 from the company Baileigh),

[0174] - polishing of the cross-section of the CVR monofilaments to a final particle surface of 0.25 μm using a mechanical polisher from the company Mecapol,

[0175] -Using a gold sputtering coater (from the company 108 or 208 series Cressington coater) applies 1nm to 4nm of gold,

[0176] - Observation of cross sections of CVR filaments using a scanning electron microscope (15 kV) under vacuum, and

[0177] - Calculate the surface percentage of pores (% porosity = area of ​​pores / (area of ​​pores + area of ​​fibers + area of ​​cross-linked resin)) using an image processing program (eg FIJI).

[0178] Mechanical properties

[0179] According to standard ASTM D2343, the tensile strength of the coated (i.e. ready-to-use) CVR monofilaments was measured at a temperature of 23° C. using an “INSTRON” 5944 model tensile tester (supplied with the tensile tester). UNIVERSAL software) to measure the tensile mechanical properties (modulus E 23 , breaking stress Cr and breaking elongation Ar). Before the measurement, these monofilaments were subjected to pre-conditioning (storing the monofilaments for at least 24 hours in a standard atmosphere according to European standard DIN EN 20139 (temperature of 23°C ± 2°C; relative humidity of 50% ± 5%)). In order to prevent damage to the glass reinforcement when the sample is clamped in the jaws of the tensile tester, the end pieces are connected as follows (material: cardboard, 50 mm long; adhesive used: Loctite EA 9483 (two-component epoxy resin)). The surfaces of the two opposing end pieces are coated with adhesive, as are the reinforcements, thereby limiting any "dry areas" (areas without adhesive) as much as possible. The end pieces are kept in an appropriate position in a fixture with the specimen size for the curing time (12h at 23°C), with weights on the end pieces to ensure good end piece / reinforcement contact. The tensile modulus is determined by linear regression of the stress versus strain curve (between 0.1% strain and 0.6% strain). The strain is recorded by an extensometer MultiXtens 1995DA801. The tested specimen (whose length was 260 mm) was pulled at a nominal speed of 5 m / min under a preload of 0.5 MPa before the test (reference length 50 mm, distance between the jaws: 150 mm). All the results given are the average of 5 measurements.

[0180] Aging protocol in alkaline solution

[0181] A glass tube with a length of 300 mm and a diameter of 30 mm was filled with 160 mL of an alkaline solution with a pH of 13.5. A glass tube with a length of 260 mm including CVR monofilaments was kept at 60°C for 3 days and then washed with water. The monofilaments were then dried at ambient temperature and then subjected to tensile testing. At least 5 repeated tensile tests were performed and compared with tensile tests performed on monofilaments that were not subjected to the aging protocol in an alkaline solution. All results given are averages of 5 measurements. The results are presented as a percentage of the reduction in breaking stress. The smaller the percentage, the smaller the degree of reduction in breaking stress and the better the alkali resistance.

[0182] Solutions for concrete aging

[0183] Fresh commercial concrete with the trade name Ductal was prepared according to the manufacturer's recommendations, and then 3% by volume of CVR monofilaments with a diameter of 0.54 mm and a length of 18 mm were added at the end of the mixing cycle. The fresh fiber-reinforced concrete was poured into a phenolic plywood formwork to form a large plate measuring 745×540×15 mm. The mold was filled by pouring along the edges to promote the orientation of the fibers in the pouring direction. After completion, the large plate was kept at the manufacturing site under standard temperature, pressure and humidity conditions. After 24 hours, the plate was released from the mold and then placed for 14 days in a place regulated at 20°C ± 2°C and 100% RH.

[0184] The panels were then cut into small panels (called stays) measuring 325 x 50 x 15 mm in the longitudinal direction (which corresponds to the pouring direction of the fiber-reinforced concrete and therefore to the preferred orientation of the fibers).

[0185] The four stays were kept in a humid environment (temperature 20°C ± 2°C, humidity 100% RH) for another 14 days and then the corresponding 28 Mechanical testing was performed using a 4-point bending test for ageing testing.

[0186] The other four stays were immersed in hot water at 60°C ± 2°C in a climate chamber for another 98 days and then used with the corresponding 112 Mechanical testing was performed using a 4-point bending test for ageing testing.

[0187] The test specimens were subjected to a four-point bending test according to standard EN 1170-5 (1998). The results shown below correspond to the average of the individual results of these four tests.

[0188] Two features are documented:

[0189] (i) Limit of proportionality LOP, which is the average value at the end of the linear part of the stress / deflection curve in the bending test. For each filament (M4, M5), the value of the stress / deflection curve at t 28 The LOP results are shown in base 100 at t 112 Results greater than 100 indicate an improvement in the flexural strength of the concrete matrix at low strain levels.

[0190] (ii) Maximum breakage value MOR, which is the maximum average stress in the bending test. For each filament (M4, M5), the maximum stress at break of the filament concerned at t 28 The MOR results are shown in base 100 at t 112 A result of less than 100 indicates a reduction in the strength of the reinforcing fibers intended to improve flexural strength at greater strain levels.

[0191] IV-2 Testing of Monofilaments

[0192] According to the above method, CVR monofilaments (M1 to M3) according to the present invention are manufactured, wherein the running speed V of the monofilament in the irradiation chamber is ir is 100m / min, and the irradiation time of the monofilament in the irradiation chamber is D ir The irradiation chamber was 2.4 s and the length of the irradiation chamber was 4 m. The resin composition used was based on a vinyl ester resin ("ATLAC E-NOVA FW2045" from the company AOC), a triacrylate hardener ("SR 368" from the company Sartomer) and a photoinitiator ("Omnirad 819" from the company IGM). The alkali-resistant glass threads of the monofilaments M1, M2 and M3 were respectively "AR1200S" threads from the company Nippon Electric Glass (actually "AR320S-720S", "AR640S-720S" and "AR1200S-720S" threads, respectively). Table 2 below shows the diameter and tex of the monofilaments and their physical and mechanical properties.

[0193] [Table 2]

[0194]

[0195]

[0196] The porosity and breaking stress of these monofilaments are compared with prior art reinforcing fibers for concrete. It is observed that these prior art fibers systematically have a porosity greater than 2% and a breaking stress less than or equal to 1050 MPa.

[0197] CVR monofilaments (M4 and M5) were manufactured according to the above method, wherein the running speed V of the monofilament in the irradiation chamber was ir is 100m / min, and the irradiation time of the monofilament in the irradiation chamber is D ir The irradiation chamber is 2.4 s and the length of the irradiation chamber is 4 m. The resin composition used is based on a vinyl ester resin ("ATLAC E-NOVA FW2045" from the company AOC), a triacrylate hardener ("SR 368" from the company Sartomer) and a photoinitiator ("Omnirad819" from the company IGM). The alkali-resistant glass yarn of the monofilament M4 is an "AR320S720S" yarn from the company Nippon Electric Glass, which contains 17% by weight of ZrO2. The glass yarn of the monofilament M5 is an "ECR SE1200 R25H" yarn from Owens Corning. The tex of the glass fibers of the monofilaments M4 and M5 are 320 g / km and 300 g / km, respectively, and the glass fiber / resin weight ratio of the monofilaments M4 and M5 is 70 / 30, respectively. Table 3 below shows the properties of these monofilaments.

[0198] [Table 3]

[0199]

[0200] As expected, with 28 The LOP is compared to that at t 112 The results based on 100 of LOP show the improvement of the flexural strength of the concrete matrix at low strain levels during concrete aging. The fibers according to the invention do not reduce this improvement. In contrast, the fibers according to the invention (M4) significantly limit the strength reduction (MOR) of the reinforcing fibers intended to improve the flexural strength at higher strain levels. Therefore, the CVR monofilaments according to the invention provide concrete with better reinforcement over time.

[0201] Due to the low porosity and high breaking stress, the monofilaments according to the invention are able to improve the crack resistance of the concrete. Thus, it was found that the monofilaments according to the invention offer an improved compromise of properties between, in particular, mechanical strength, corrosion resistance, processability (in particular dispersion during mixing, processing temperature and homogeneity maintenance during concrete drying).

Claims

1. A method for producing a glass-resin composite monofilament comprising an alkali-resistant glass filament embedded in a cross-linked resin, the alkali-resistant glass filament containing 5 to 30% by weight of ZrO2, the method comprising the following consecutive steps: - forming a linear arrangement of alkali-resistant glass threads containing 5 to 30% by weight of ZrO2 and conveying this arrangement in the feed direction, - degassing the arranged glass threads by the action of vacuum in a vacuum chamber, - at the outlet of the vacuum chamber, after degassing, passing through a vacuum impregnation chamber to impregnate the arranged glass filaments with a photocurable resin composition called "impregnation resin" in a liquid state, thereby obtaining a prepreg comprising the glass filaments and the resin composition, - passing the prepreg through a shaping die having a cross-section with a predetermined area and shape so as to give it a monofilament shape, - Downstream of the die, the resin composition is polymerized under the action of ultraviolet rays in a UV irradiation chamber, the irradiation chamber comprising a tube transparent to ultraviolet rays, called an irradiation tube, through which the monofilaments to be formed are passed and through which a stream of inert gas flows, the running speed of the monofilaments through the irradiation chamber (denoted by V ir ) is greater than 50m / min, the irradiation time of the monofilament in the irradiation chamber (expressed as D ir ) is equal to or greater than 1.5s, - The monofilaments are cut into lengths ranging from 5 mm to 85 mm.

2. The method according to claim 1, characterized in that The diameter of the monofilaments ranges from 0.2 mm to 1.3 mm, preferably from 0.25 mm to 1.25 mm, preferably from 0.3 mm to 1.2 mm.

3. The method according to any one of the preceding claims, characterized in that The length of the cut monofilaments is in the range of 10 mm to 80 mm, preferably 15 mm to 60 mm.

4. The method according to claim 3, wherein: The length / diameter ratio of the monofilaments ranges from 10 to 110, preferably from 20 to 90, and more preferably from 25 to less than 80.

5. The method according to any one of the preceding claims, characterized in that The alkali-resistant glass yarn contains 6 to 22% by weight, preferably 10 to 20% by weight, of ZrO2.

6. The method according to any one of the preceding claims, characterized in that The alkali-resistant glass yarn accounts for 65 to 85% by weight, preferably 70 to 80% by weight of the monofilament, and the cross-linking resin accounts for 15 to 35% by weight, preferably 20 to 30% by weight of the monofilament.

7. The method according to any one of the preceding claims, characterized in that The impregnating resin is based on at least: - a crosslinkable resin selected from the group consisting of vinyl ester resins, epoxy resins, polyester resins and mixtures thereof, - a cross-linking system comprising a photoinitiator, which is reactive to UV radiation above 300 nm.

8. Monofilament obtainable by the method according to any one of claims 1 to 7.

9. The monofilament according to claim 8, characterized in that The porosity of the monofilaments is less than 2%, preferably less than 1%, preferably less than 0.5%.

10. The monofilament according to any one of claims 8 and 9, characterized in that The breaking stress of the monofilament is greater than 1050 MPa, preferably greater than or equal to 1100 MPa, and more preferably greater than or equal to 1200 MPa.

11. The monofilament according to any one of claims 8 to 10, characterized in that The monofilament measured at 23°C is denoted as E 23 The initial tensile modulus is greater than 35 GPa, preferably greater than 40 GPa.

12. A tow comprising a plurality of monofilaments according to any one of claims 8 to 11 and at least one rupturable membrane holding the monofilaments together, the rupturable membrane preferably being a water-soluble membrane made of a material selected from polyvinyl alcohol (PVA).

13. The tow according to claim 12, wherein The number of monofilaments ranges from 300 to 20,000.

14. Use of a monofilament according to any one of claims 8 to 11 or a tow according to any one of claims 12 and 13 for reinforcing concrete and / or reducing the weight of concrete and / or reducing or preventing cracking of concrete.

15. Concrete comprising a plurality of monofilaments according to any one of claims 8 to 11, wherein the volume ratio of the monofilaments in the concrete is preferably in the range of 0.1% to 6%.

Citation Information

Patent Citations

  • Method for manufacturing highly stressed composite pieces

    EP1074369A1

  • Pneumatic tyre reinforced by composite element and such composite element

    EP1167080A1

  • Continuous resin impregnation of very long fibres for the manufacturing of elongated composite elements

    EP1174250A1

  • FR2644449A1

  • Glass composition resistant to chemical media, useful to produce reinforcing yarns, comprises silica, zirconium oxide, lithium oxide, potassium oxide, sodium oxide, calcium oxide and another metal oxide

    FR2907777A1